A Validation Study of a Self-Assessment Questionnaire for Middle School Students' Self-Presentation Skills - Tong, Weiwei (Naifaderu Cipta Sejahtera, 2024)
Purpose This study validates a self-assessment questionnaire to measure middle school students' self-presentation skills. Methodology The questionnaire was developed based on a comprehensive literature review and expert consultations. A sample of 200 students from two representative junior high schools in Fuzhou, China, participated in the study. The questionnaire underwent expert content validity assessment, and revisions were made based on the experts' feedback. Results/Findings The final questionnaire consists of 13 items. The reliability of the questionnaire was assessed using Cronbach's alpha, resulting in a value of 0.778, indicating good internal consistency. The Kaiser-Meyer-Olkin (KMO) measure of sampling adequacy was 0.818, suggesting good sample fitness for factor analysis. Bartlett's test of sphericity yielded a statistic of 807.915, supporting the appropriateness of factor analysis. These results demonstrate that the questionnaire is reliable and valid for assessing middle school students' self-presentation skills. Implications This study provides a valuable tool for both researchers and practitioners interested in understanding and fostering adolescents' social and personal development